2021
DOI: 10.1097/j.pain.0000000000002437
|View full text |Cite
|
Sign up to set email alerts
|

To tolerate weather and to tolerate pain: two sides of the same coin? The Tromsø Study 7

Abstract: Supplemental Digital Content is Available in the Text. The temporal nonrandom variation in pain tolerance and the associations with meteorological variables suggest that weather has a causal and dynamic effect on pain tolerance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Thus, the subjective experience of the environment might be an important marker for the cold exposures’ effect on the body, but a poor marker of the thermal environment. On the other side, the experience of pain and the environment, as well as having pain, could very well be closely connected ( Sundstrup et al, 2015 ; Farbu et al, 2021b ). The central sensitization associated with pain could increase the risk of feeling cold or cooling, and the likelihood of reporting a cold environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the subjective experience of the environment might be an important marker for the cold exposures’ effect on the body, but a poor marker of the thermal environment. On the other side, the experience of pain and the environment, as well as having pain, could very well be closely connected ( Sundstrup et al, 2015 ; Farbu et al, 2021b ). The central sensitization associated with pain could increase the risk of feeling cold or cooling, and the likelihood of reporting a cold environment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many report that their pain condition is aggravated by weather ( Timmermans et al, 2014 ) and that cold temperature causes pain. Further, the findings that weather affects pain tolerance indicates that the climatic environment can be of importance for how and when we feel pain ( Farbu et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,11,46,49 Accordingly, in the large-scale Tromsø study, cold weather acclimatization matched cold pain tolerance. 25 Although these mechanisms may play a role, they do not explain our findings because peripheral vascular responding was not correlated and thus likely not causally related to perceived cold-pressor–induced pain. Previous studies found that direct microneurographically recorded human cutaneous sympathetic activity during a cold-pressor test was weak, inconsistent, and not correlated to pain.…”
Section: Discussionmentioning
confidence: 74%
“…It is a common belief is that the weather affects pain. Pressure pain tolerance and cold pain tolerance correlate with meteorological variables, and these findings suggest that weather has a causal and dynamic effect on pain tolerance [ 20 ]. Alterations in barometric pressure (BMP) have also been associated with triggering tension-type headaches but multiple studies have been performed with inconsistent results [ 21 ].…”
Section: Reviewmentioning
confidence: 99%